Activity of Various Cathepsin Proteases and Enrichment of Klotho Protein in the Urine and Urinary Extracellular Vesicles After SARS-CoV-2 Infection - Niharika Bala; Ramish H. Rafay; Sarah C. Glover; Abdel A. Alli (Viruses)
Background: The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is responsible for causing the Coronavirus disease 2019 (COVID-19) outbreak. While mutations cause the emergence of new variants, the ancestral SARS-CoV-2 strain is unique among other strains. Methods: Various clinical parameters, the activity of cathepsin proteases, and the concentration of various proteins were measured in urine samples from COVID-19-negative participants and COVID-19-positive participants. Urinary extracellular vesicles (uEVs) were isolated from urine samples from the two groups and used for proteomic analysis and subsequent pathway analyses. Results: Activity levels of cathepsin S and L were greater in the urine of COVID-19-positive participants. The concentration of C-reactive protein, transmembrane serine protease 2, and klotho protein were significantly greater in the urine of COVID-19-positive participants. There was a greater amount of uEVs in the COVID-19 group and klotho protein was found to be enriched in uEVs from the COVID-19 group. Pathway analyses of the proteomics data showed most of the identified proteins were involved in signal transduction, stress response, protein metabolism, and transport. The identified proteins were predominantly associated with cellular membranes and with function of the cytoskeleton, enzyme regulation, and signal transduction. Conclusions: Taken together, our data identify novel urinary biomarkers that could be used to further investigate the long-term effects of SARS-CoV-2 infection.